ANALISIS TEMA DAN FAKTA CERITA DALAM FILM KOREA SESANGESEO GAJANG AREUMDAUN IBYEOL - , ADINDA AMALIA INSANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper titled âAnalisis Tema dan Fakta Cerita dalam film Sesangeseo Gajang Areumdaun Ibyeol.â The objective of this study is to find the theme and facts of the story. This story was chosen as the object of the study because the story is easy to understand and the story is close to everyday life. Additionally it contains pictures of the life story in Korean family. The paper is analyzedusing Robert Stantonâs and Burhan Nurgiyantoroâs fiction analysis theory. The result of this study shows thatthe traditional theme of the film isâaffection towards familyâ, while non- traditional theme is âmain role died in the endingâ.The plot of the story is progressive. The main character in this film is Kim In-Hee and Jung-Chul. Setting of place in the movie is in public places makes this movie seems more natural and real as if in everyday life. The setting is in winter time in Korea and the social background is the difference in social status between 2 siblings.